The Influence of Mind Mapping in Teaching Reading Comprehension to the Eighth Grade Students of SMP Muhammadiyah 1 Rawa Bening - Andriani, Dwi (Titian Ilmu: Jurnal Ilmiah Multi Sciences, 2017)
The objectives of this study is: Ã¢â¬Åto find out whether or not there Is the influence between the students who are taught by using mind mapping technique and who are not taught  by using mind mapping technique Ã¢â¬Â. The 60 samples out of 120 students from the eighth grade students were chosen by means  purposive sampling technique. It used quasi-experimental method, nonrandomized pretest and posttest design. The data was analyzed using independent  t-test for SPSS. The result showed that t-obtained was 6.20, while t-table was 2.04. it means that there was the influence between the students who were taught by using mind mapping technique and who were not taught  by using mind mapping technique.